Psycholinguistic Manifestations of Students’ Information Stance As to the Types of Social and Psychological Maturity - Shyshkina, Khrystyna (East European Journal of Psycholinguistics, 2014)
The current stage of development of psycholinguistics, which seeks the solution to the increasingly complex problems of the individual and society, requires the study of social and psychological maturity of the individual. In an analysis of the main areas of research are needed to study information stance, which is manifested in the social and psychological maturity of the students, in terms of psycholinguistics. The main source of its formation is argued a system of values, professional and life experience, personality philosophy, acquired knowledge, skills concerning information. In carrying out her own internal human potential in personal, social and professional spheres, information stance serves as a fundamental factor. The results of theoretical and empirical research of psycholinguistic features of students’ information stance are highlighted in the article. Theoretical justification and empirical investigation of information stance in accordance with types of social and psychological maturity of the students are realized. References Baranov, A. N. (2013) Vvedenye v prykladnuyu lynhvystyku [Introduction to Psycholinguistics] Moscow: Librokom. Zasiekin, S. V. (2012) Psykholinhvistychni Universaliyi Perekladu Khudozhnioho Tekstu [Psycholinguistic Universals in the Translation of Literary Text]. Lutsk: Lesya Ukrainka Volyn National University. Zasiekina, L. V, Zasiekin, S. V. (2008) Psykholinhvistychna diahnostyka [Psycholinguistic Diagnostics]. Lutsk: Vezha Publishers of Lesya Ukrainka Volyn National University. Austin, J. (1986) Slovo kak deystvye [Word as Action]. Novoe v Zarubezhnoy Lingvistike, Vol. 17. Moscow: Progress, 22-131. Ushakova, T. N. (2006). Psikholingvistika [Psycholinguistics], T. N. Ushakova, Ed. Moscow: PerSe. Leontyev, A. A. (2003). Psykholynhvystycheskaya Ekspertyza Ksenofobyy v Sredstvakh Massovoy Informatsyy [Psycholinguistic Expertise of Xenophobia in Mass Comunications]. Moscow: Smysl. Khvorost, K. (2012) The impact of information of political discourse on individual. In: Applied Psycholinguistics: Positive Effects and Ethical Perspectives., G. Mininni, A. Manuti, Eds. Milano: FrancoAngeli. 2, 295–305.